SCIENTIFIC SUBSTANTIATION OF REGULATING EUTROPHICATION PROCESSES OF WATER OBJECTS (ON THE EXAMPLE OF THE VORSKLA RIVER) - Korchahin, O. P. (Scientific Progress & Innovations, 2020)
The article deals with investigating eutrophication process of water eco-systems. It has been mentioned that at present the development of theoretical foundations and search of practical measures in fighting mass development of cyanic bacteria in top layer water reservoirs are being actively conducted. At the same time, using bacteria for purification of surface water objects is insufficiently researched at present, so the need for studying eutrophication processes of water objects while using different methods of biological purification, arises. Thus, the purpose of the work was investigating chemical and biological methods of water objects’ restoration by decreasing the amount of cyanic bacteria in them. Based on the conducted research, scientific recommendations have been proposed as to fighting surface water reservoirs’ blooming. The investigation methods included conducting analytical, natural, laboratory studies, as well as calculation part. To investigate eutrophication process of water in the Vorskla river, samples were taken 0.2-0.5 m deep from the water reservoir top layer (in different districts of the city of Poltava and its outskirts). During the first stage of investigation, chemical methods of fighting water blooming were studied. The best result was achieved at applying potassium permanganate (0.2*106 cl/l), molybdenum liquid (0.3*106), magnesia mixture (0.4*106), chlorine (0.5*106), and ferrum chelate (0.6*106). During the second research stage, studying probiotics influence in fighting water blooming as to toxic effect to cyanic bacteria was conducted. It has been established that using biological methods of water objects’ purification from cyanic bacteria are more effective in comparison with chemical methods. In particular, applying Sviteko-Agrobiotic-01 probiotic is 94% effective in eliminating cyanic bacteria. The same result was obtained while using potassium permanganate (0.2*106). However, the negative effect of the mentioned above chemical method is that it results in secondary water reservoir pollution. The effectiveness of other chemical methods in fighting water blooming was also determined: molybdenum liquid (91 % effectiveness), magnesia mixture (88 %), chlorine (85 %), and ferrum chelate (82 %). Somewhat worse results were achieved at applying argentum nitrate (70 %) and barium chloride (41 %). The largest amount of blue-green algae remained active at using aluminum sulfate in combination with copper sulfate (26 % effectiveness). The conducted studies are basis for working out complex systems of water eco-systems’ purification from cyanic bacteria using environmentally safe methods, which are one of the priority development of urbanized territories and sustainable development of the society.